Интродукция и перспективы использования в зеленом строительстве Magnolia kobus DC. на юго-востоке Украины - Суслова, Е.П. (Промышленная ботаника, 2006)
Results of generative development studying and assessment of perspective of Magnolia kobus DC. using in urban greening in the south-east of Ukraine are presented. Morphogenesis of Magnolia kobus DC. generative buds, its pollen grains viability and seed quality were studied. Methods of seed presowing treatment were fixed. Conclusion is made as for the species tolerance under introduction conditions and perspective of its using in greenery planting of the region.